2022
DOI: 10.3389/fnhum.2022.901387
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a New Lightweight EEG Technology for Translational Applications of Passive Brain-Computer Interfaces

Abstract: Technologies like passive brain-computer interfaces (BCI) can enhance human-machine interaction. Anyhow, there are still shortcomings in terms of easiness of use, reliability, and generalizability that prevent passive-BCI from entering real-life situations. The current work aimed to technologically and methodologically design a new gel-free passive-BCI system for out-of-the-lab employment. The choice of the water-based electrodes and the design of a new lightweight headset met the need for easy-to-wear, comfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…Results demonstrated the reliability of the proposed EEG-based distraction index in identifying the drivers’ distraction while driving along different conditions, representing a synthetic, objective, and more ecological solution with respect to the largely validated subjective and behavioral measurements. More importantly, the technical implementation of the proposed index allows for the driving distraction online evaluation while driving, even in real context since the proposed index was derived from EEG signal collected through a wearable EEG system, which was demonstrated to be reliable and compatible with out-of-the-lab applications [ 35 ]. In summary, this study, alongside its findings, lays the groundwork for integrating neurophysiological evaluation of driving distraction into real-world settings to enhance road traffic safety, as well as a powerful tool for further investigation of the driver’s psychology and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Results demonstrated the reliability of the proposed EEG-based distraction index in identifying the drivers’ distraction while driving along different conditions, representing a synthetic, objective, and more ecological solution with respect to the largely validated subjective and behavioral measurements. More importantly, the technical implementation of the proposed index allows for the driving distraction online evaluation while driving, even in real context since the proposed index was derived from EEG signal collected through a wearable EEG system, which was demonstrated to be reliable and compatible with out-of-the-lab applications [ 35 ]. In summary, this study, alongside its findings, lays the groundwork for integrating neurophysiological evaluation of driving distraction into real-world settings to enhance road traffic safety, as well as a powerful tool for further investigation of the driver’s psychology and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Among the relevant thirteen studies, reproducibility was demonstrated for different electrode configurations and preprocessing pipelines (Mastropietro et al, 2023 ), for different settings of 2D and 3D environments (Kakkos et al, 2019 ), for a larger number of participants (Radüntz et al, 2020 ), for different tasks (Parekh et al, 2018 ; Boring et al, 2020 ; Sciaraffa et al, 2022 ), and over time (Gevins et al, 1998 ; Putze et al, 2013 ; Aricò et al, 2015 , 2016b ; Ortiz et al, 2020 ; Fox et al, 2022 ; Roy et al, 2022 ). Gevins et al ( 1998 ) also tested their findings on separate tasks to check cross-task performance and finally on data from a new participant to observe cross-subject performance.…”
Section: Reproducibility In Mental Workload Studies Using Eegmentioning
confidence: 99%
“…EEG-based BCI systems that manipulated motor imagery signals generated through the movements of large body parts such as hands, feet, and tongue have been proposed to control assistive devices throughout the past several decades (Pfurtscheller and Neuper, 2001 ; Alazrai et al, 2019 ; Degirmenci et al, 2023 ). However, such systems propose only limited control dimensions for prosthetic devices, thereby, the potential of utilizing these systems to control further complex assistive devices is restricted (Sciaraffa et al, 2022 ). In the last decade, numerous research studies have examined the decoding of movements of fine body parts to improve such systems (Alazrai et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%